Random telegraph noise in SiGe HBTs: Reliability analysis close to SOA limit. (June 2017) - Mukherjee, C.; Jacquet, T.; Chakravorty, A.; Zimmer, T.; Boeck, J.; Aufinger, K.; Maneux, C.
Abstract: In this paper, we present extensive random telegraph signal (RTS) noise characterization in SiGe heterojunction bipolar transistors. RTS noise, observed at the base, originates at the emitter periphery while at the collector side distinct RTS noise is observed at high-injection that originates from the traps in the shallow trench regions. Time constants extracted from RTS during aging tests allow understanding of trap dynamics and new defect formation within the device structure. This paper provides the first demonstration of RTS measurements during accelerated aging tests to study and understand generation of defects under bias stress in SiGe HBTs operating at the limit of their safe-operating area. Highlights: Hot carrier degradation is studied in SiGe HBTs under high electrical stress conditions beyond the safe operating area. Hot carrier degradation is analyzed using RTS. Locations and dynamics of failure mechanisms at the base and collector are studied and analyzed using RTS. Evolutions of base and collector RTS time constants under the stress conditions are studied. RTS noise characterization is demonstrated as an efficient reliability indicator for the major known defects in SiGe HBTs.